1993
DOI: 10.1007/bf00762460
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial NADH-quinone oxidoreductases: Iron-sulfur clusters and related problems

Abstract: Many bacteria contain proton-translocating membrane-bound NADH-quinone oxidoreductases (NDH-1), which demonstrate significant genetic, spectral, and kinetic similarity with their mitochondrial counterparts. This review is devoted to the comparative aspects of the iron-sulfur cluster composition of NDH-1 from the most well-studied bacterial systems to date.: Paracoccus denitrificans, Rhodobacter sphaeroides, Escherichia coli, and Thermus thermophilus. These bacterial systems provide useful models for the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
2
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 70 publications
4
75
2
1
Order By: Relevance
“…Despite having about half the molecular mass of complex I and a third of its subunits, the P. denitrificans NDH1 contains the same set of redox centres [6,7]. Furthermore, the EPR spectra of all the detectable Fe-S clusters in P. denitrificans NDH1, unlike those of E. coli, are very similar to the respective clusters in complex I [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite having about half the molecular mass of complex I and a third of its subunits, the P. denitrificans NDH1 contains the same set of redox centres [6,7]. Furthermore, the EPR spectra of all the detectable Fe-S clusters in P. denitrificans NDH1, unlike those of E. coli, are very similar to the respective clusters in complex I [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent study on the isolated enzyme, three different binuclear clusters were reported [6]. One of them, Nla, has a very low midpoint potential and is thus expected to be EPRinvisible under the conditions used here.…”
Section: Resultsmentioning
confidence: 81%
“…The second one was named N 1 b (gX,Y.Z = 1.94, 1.94, 2.03), due to its similarity to the mitochondrial cluster 1 b. The third binucfear cluster, named Nlc &X,Y,Z = 1.92, 1.95, 1.99>, is unique to E. coZi NDHl and no homologous cluster is currently known in any other enzyme of this family [6]. change during long incubation [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations